Experimental study of shale-fluids interaction during oxidative dissolution with hydrogen peroxide, sodium hypochlorite and sodium persulfate. (February 2020) - Li, Yilian; Yang, Sen; Liu, Danqing; Yang, Cong; Yang, Zhe; Li, Hai; Tang, Zhi
Abstract: The drastic decline of shale gas production after fracturing depresses the development of this unconventional gas resource. Although shale oxidant stimulation can dissolve unstable composition to enhance permeability, the shale-fluids interaction during this stimulation process is still not yet clear. In this study, the organic-rich shale collected from the Cambrian Shuijingtuo Formation of Yichang, Hubei province, China was selected to react with three oxidants, hydrogen peroxide (H2 O2 ), sodium hypochlorite (NaClO) and sodium persulfate (Na2 S2 O8 ) at formation temperature. Variation of water chemistry, mineral composition and micromorphology were analyzed to reveal the mechanism of shale oxidative dissolution and evaluate its influence on shale permeability enhancement. Results showed that pyrite and OM can be discrepantly oxidized with different oxidants. At the same oxidation duration, the acidic environment was beneficial for carbonate dissolution, while the alkaline environment was favorable to the dissolution of dolomite and tectosilicate minerals such as quartz, albite, illite and chlorite. Nevertheless, the serious thermal decomposition of H2 O2, precipitation of gypsum and ferric hydroxide (Fe(OH)3 ) occurred during shale-fluids interaction at formation temperature might impede the enhancement of shale permeability. The oxidative dissolution of shale also brought about the release of trace elements, which might result in groundwater pollution. For the in-situ application of shale oxidative dissolution, difficulties such as thermal decomposition, secondary minerals precipitation and possible groundwater pollution should be considered further in the future. Highlights: Shale can be stimulated with the oxidative dissolution of pyrite and organic matter. NaClO has advantages in oxidizing both pyrite and organic matter over H2 O2 and NaS2 O8. Precipitation of gypsum and ferric hydroxide may impede the enhancement of shale permeability during oxidative dissolution.